Notes on the genus Pseudoliparis (Orchidaceae, Malaxidinae), with description of a new species from New Guinea and a new synonymous name - Margońska, Hanna B. (Phytotaxa, 2020)
At present, Pseudoliparis Finet (1907: 536) includes about 44 species, but nearly a quarter of these have been described relatively recently. The species of Pseudoliparis are generally poorly known and represented in herbaria and liquid collections. Many species are still known from only a few specimens or just the type-collection/protologue (e.g. especially some of Schlechter’s species). Their distribution also contributes to making them poorly known: tropical regions of Southeast Asia through Micronesia, especially New Guinea and the surrounding islands. Knowledge of their ecology, phenology and occurrence is limited as well. However, recent research clearly shows that their floral morphology and coloration and records about their olfactory characteristics are adaptations to specific pollinators, probably small Diptera or Hymenoptera, which promote reproductive their isolation.